FEATURES ENDOCRINE PATHOLOGY AMONG STUDENTS OF TOMSK - P. R. Goldayeva; O. A. Pavlenko (Бюллетень сибирской медицины)
Socio-hygienic assessment of the health of students inTomskfor the period from 2007 to 2009 helped identify negative trends in the incidence of endocrine disorders that require improved technology organization providing medical and preventive care. The results of the analysis of the effect of risk factors on the development of the endocrine pathology among students possible to determine the need for and develop a system of sanitary measures, the implementation of which helps reduce the risk of endocrine diseases and improve preventive work among the students of Tomsk.